Public management reform : a comparative analysis : new public management, governance, and the neo-Weberian state - Pollitt, Christopher (Oxford University Press, 2011)
Since its publication in 2000, Public Management Reform has established itself as the standard text in the field, presenting a comparative analysis of recent changes in Public Management and Public Administration in a range of countries in Europe, North America, and Australasia. This third edition has been completely rewritten to incorporate a mass of recent empirical data and to introduce a new theoretical and conceptual framework by identifying three leading visions of reform. Chapters analyse key debates, the process of change, different national systems and trajectories, results, political factors, and paradoxes and trade-offs in an integrated volume. Covering reforms over a thirty-year period (1980-2010), the book offers a detailed and structured comparison of twelve countries and the EU Commission by means of an unparalleled synthesis of evidence and sources. Extensive factual appendices provide an invaluable resource for students.